Pentingnya Gizi Seimbang untuk Mencegah Dampak Buruk Stunting pada Kesehatan dan Perkembangan Anak Sejak Dini: The Importance of Balanced Nutrition to Prevent the Bad Impact of Stunting on Children's Health and Development from an Early Age - Ariska, Karin; Maharani, Rivana; Nuraini, Lisa (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
According to result of 2022 Indonesian Nutritional Status Survey, stunting rates in Indonesia is quite high especially at 21.6 %. Eventhough it decreased by 24.4 % in 2021 compared to previous year, this is relatively high score. Stunting is the condition where babies are taller or shorter than their age. It is measured by the the height that exceeded minus two standard deviations from average growth standard of WHO for children. Stunting in the infants is the chronic nutritional problems caused by several factors including socio-economic condition, infant pain and poor nutritional intake and maternal diet during pregnancy. In future, stunted babies will have some difficulties in achieving optimal cognitive and physical development. Stunting had impacts on children's health. Stunting can expand a risk of infection and disease, reduce mental performance, reduce economic productivity and fertility, and increase a risk of chronic diseases. An impact of stunting can be felt in the long and short term.